Perlindungan Hukum Terhadap Anak Sebagai Saksi Dalam Proses Peradilan Pidana Di Indonesia - Alputila, Marlyn Jane; Sinaga, Jaya Setiawan (Universitas Musamus, 2025)
This study aims to analyze the forms and mechanisms of legal protection for children as witnesses in the criminal justice process in Indonesia, as well as to identify obstacles and solutions in its implementation. The research method employed is a normative juridical approach with a literature study on relevant legislation and related literature. The results show that legal protection for child witnesses is comprehensively regulated in the Child Protection Act and the Juvenile Criminal Justice System Act, including rights to accompaniment, child-friendly examination, and provision of special facilities. However, implementation in the field faces challenges such as lack of training for law enforcement officers, inadequate facilities, weak inter-agency coordination, and cultural and social factors. Therefore, it is necessary to improve human resource capacity, institutional strengthening, and legal education to the public to ensure effective protection of children as witnesses. This study concludes that legal protection for child witnesses is an important indicator of a fair and civilized justice system in Indonesia. Keywords: children, witnesses, legal protection, criminal justice, Indonesia